The Harmony between Ukrainian and European Values - Dodonova, Vira (Skhid, 2025)
This article is devoted to the problem of comparing Ukraine’s national values with European values. According to the Law of Ukraine “On National Security”, Ukraine’s national security is defined as “the protection of state sovereignty, territorial integrity, democratic constitutional order, and other national interests of Ukraine from real and potential threats”. Experts rightly criticise this definition for being incomplete, since national values are no less important than interests. Values are also not mentioned in the Law of Ukraine “On the Basic Principles of State Policy in the Sphere of Establishing Ukrainian National and Civic Identity”. However, interests need to be complemented by values, as national interests in today’s world can change rapidly under the influence of external and internal circumstances, while values are a stable foundation for statehood. Ukraine’s strategic orientation towards European integration involves comparing Ukrainian and European values as part and whole. The basis of this process is a dialogue between European and Ukrainian cultural values. The system of values is revealed: a meaningful life, a vital system, an interactional, and a socializational system. To the usual complex of European values, such as freedom, democracy, and equality, others are added: "inner world", "deep respect for ordinary life", "self-fulfillment", as well as "freedom", "acceptable difference" and "practical rationalism of world domination". Among the Ukrainian values, the following are being analyzed: "desire for Order", "heartiness and sincerity", "freedom", "a feeling of a special connection with the environment", "a feeling of involvement in the affairs of other people", "the ability to overcome geopolitical traumas". Ukrainian cultural values are an open system, complemented by other components. Demonstrating the similarity between Ukrainian and European values in the table, the author concludes that the similarity of cultures makes Ukraine an integral part of the European sociocultural space.